PENGARUH PEMANFAATAN DANA ZAKAT PRODUKTIF TERHADAP TINGKAT PENDAPATAN MUSTAHIK: Studi Kasus pada Badan Amil Zakat Nasional di Kecamatan Haurgeulis, Kabupaten Indramayu - Syatir Maufur; Irvan Iswandi (Melati Institute, 2022)
In Islam, we are familiar with zakat, which is one of the five pillars of Islam. In essence, zakat is a certain part of the property of a person who is Muslim which must be issued by order of Allah SWT, for the benefit of others according to a predetermined level. Zakat is issued with the aim of cleaning up the property of the owner then as gratitude for the blessings that have been given. By adhering to the aqidah or belief that is spread by Islam for humans, the way is opened to achieve the goodness of life in this world and goodness in the hereafter, after humans leave this mortal world. This study aims to determine whether there is an effect of the use of productive zakat on the income level of the Mustahik who are on the mustahik list of BAZNAS, Haurgeulis District. The implementation of this research was carried out from January to d. March 2018. The respondents who were taken were 30 people who were included in the mustahik list of BAZNAS, Haurgeulis District, using the non-probability sampling method. This research method is quantitative by collecting data used by the method of questionnaires, observation and literature study. The results of this study are to analyze the data used percentages based on statistical analysis with technical analysis ANOVA using SPSS 20.0 for windows program. Based on the coefficient table through the calculation of SPSS version 20.00, the t value for the variable X (utilization of productive zakat funds) is 24.606. While the value of t table for N = 30 is 0.294. so t count > t table or 24.606> 0.294 with probability (significance) = 0.05%. Thus, Ho is rejected and H1 is accepted. Because the value of t count > t table, it can be concluded that the utilization of productive zakat funds (Variable X) does have a positive and significant effect on the income level of mustahik (Variable Y). So here it is clear that the proposed hypothesis is proven true. Based on calculations using (SPSS)version 20.00, namely the ANOVA test or F test, it was found that the Fcount was 11,915 while the F table (a 0.05) for N = 30 was 2.69. So the calculated F is greater than F table or 11.915> 2.69 with a significant level of 0.00 because 0.00 < 0.05, it can be said that the variable utilization of productive zakat funds (X) simultaneously has a real influence on the level variable. income (Y) on mustahik in the National Amil Zakat Agency, Haurgeulis District.